Hubungan Kekuatan Otot Tungkai Dengan Kecepatan Lari 100 Meter Siswa Kelas XI - Budiyanto, Budiyanto; Febrianti, Riska Ayu; Ladjiku, Akram; Rastini, Rastini; Tahir, Nandar; Umar, Is Suleman; Hidayat, Joni Taufik; Ikhsan, Haerul; Ilham, Al (Universitas Negeri Gorontalo, 2025)
This study aims to determine how strong the relationship is between leg muscle strength and 100-meter running speed in class XI students at SMA Negeri 3 Gorontalo. The hypothesis in this study is